1997
DOI: 10.1016/s0167-6296(96)00532-2
|View full text |Cite
|
Sign up to set email alerts
|

Income-related inequalities in health: some international comparisons

Abstract: This paper presents evidence on income-related inequalities in self-assessed health in nine industrialized countries. Health interview survey data were used to construct concentration curves of self-assessed health, measured as a latent variable. Inequalities in health favoured the higher income groups and were statistically significant in all countries. Inequalities were particularly high in the United States and the United Kingdom. Amongst other European countries, Sweden, Finland and the former East Germany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
377
4
11

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 548 publications
(410 citation statements)
references
References 20 publications
11
377
4
11
Order By: Relevance
“…25 For example, low income men are likely to present with later stage cancers. 8 Neighborhood-level inequities include unequal access to and quality of primary and secondary healthcare services 32 and may affect the relationship between prostate cancer screening and affordability of private health insurance. 8,33 Opportunistic screening through PSA testing became commonplace in the US at the end of the 1980's and in Sweden in the early 1990's.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 For example, low income men are likely to present with later stage cancers. 8 Neighborhood-level inequities include unequal access to and quality of primary and secondary healthcare services 32 and may affect the relationship between prostate cancer screening and affordability of private health insurance. 8,33 Opportunistic screening through PSA testing became commonplace in the US at the end of the 1980's and in Sweden in the early 1990's.…”
Section: Discussionmentioning
confidence: 99%
“…34 In Sweden, medical care is provided to all permanent residents, and primary healthcare clinics and hospitals are equally distributed and located centrally in all types of neighborhoods. 32 However, the actual number of health professionals working in primary healthcare clinics can vary considerably by neighborhood type. This is due to difficulties in recruiting and retaining healthcare personnel in high-deprivation neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
“…A large amount of literature shows a positive correlation between socioeconomic status and health in adulthood (Adler et al, 1994;Deaton and Paxson, 1998;Deaton and Paxson, 1999;Van Doorslaer et al, 1997;Wilkinson and Marmot, 2003). Recent research initiated by Case et al (2002) investigates whether the gradient in general health observed in adulthood has antecedents in childhood.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of empirical work in developed and developing countries has focused on measuring and explaining socioeconomic inequalities in various dimensions of health (e.g., Acheson 1998; Schalick and others 2000; van Doorslaer, Wagstaff, and Bleichrod 1997;. 1 Some research has also focused on socioeconomic inequalities in the distribution of health services or public spending on health care.…”
Section: Introductionmentioning
confidence: 99%